If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2x + 6y = -1 Solving 2x + 6y = -1 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-6y' to each side of the equation. 2x + 6y + -6y = -1 + -6y Combine like terms: 6y + -6y = 0 2x + 0 = -1 + -6y 2x = -1 + -6y Divide each side by '2'. x = -0.5 + -3y Simplifying x = -0.5 + -3y
| x^2+8x+4=9 | | -16n+4=-12n-16 | | y=20+-3x | | 4(7c-1)-2=26c+4 | | 2x^2-9=1 | | 6y-2(y-2)+5= | | 5e+12= | | 4x-4b+x^2b-x^3=0 | | (x+3)=(3x-91) | | (2x+1)=(3x-4) | | ax-bx-a^2+b^2=2a-2b | | ax-bx-a^2+b^2=2ab-2b | | (2x+15)=(6x-57) | | x^7=16870 | | x-2=.5x+5 | | 9y^3-7=y-63y^2 | | .75x-.25x+5=27 | | x-4=25/5 | | 4+5x=-4(-7x-1) | | 4q+1-5q-1= | | 4x^2-1=10x | | z+1=.5z+4 | | 7x-21y=10x+-45y | | 2(-4-x)= | | 12x^2-13x-1=0 | | -4(2+x)= | | xxx=9 | | 2(-4+x)= | | 12x^2-13x=1 | | 5(3a-6)5a=-12+a | | 5n^2+75n=3500 | | 5+29t-16t^2=12 |